Nonunique Coincidence Point Results via Admissible Mappings. (29th March 2021) - Karapınar, Erdal; Chen, Chi-Ming; Fulga, Andreea
Abstract : This paper is aimed at presenting some coincidence point results using admissible mapping in the framework of the partial b -metric spaces. Observed results of the article cover a number of existing works on the topic of "investigation of nonunique fixed points." We express an example to indicate the validity of the observed outcomes.